Will Bivalent Vaccination against COVID-19 Increase the Desire for COVID-19 Vaccination among Poles? - Mateusz Babicki (Vaccines, 2022)
Tduration of persistent protection after vaccination against COVID-19 is the sum of many factors, including the used formulation, the vaccination schedule, individual predisposition, clinical status and the SARS-CoV-2 variant. (There is a tendency that?) vaccination regimens demonstrate lower levels of immunity against the currently predominant Omicron variant, which results in the need for subsequent booster doses. Thus, bivalent formulations have been recently developed to additionally target the Omicron variant. Accordingly, the purpose of this study was to assess whether bivalent vaccines would increase interest in vaccination among Poles. For this purpose, an original questionnaire distributed via the Internet and targeting Poles over the age of 18 was used. Results: The survey included 594 respondents, the vast majority of whom were women (79.3%), residents of large cities (44.7%) and those with a university education (86.3%). The average age was 36.6 ± 9.67 years. Only 48.7% of respondents had heard of bivalent vaccination against COVID-19. 408 (72.3%) respondents confirmed that if they had the choice, they would opt for the bivalent preparation. People who have already taken at least 1 booster dose are by far the most common group. Among the unvaccinated, the percentage is only 8.9%. For 190 (33.7%) of respondents, the availability of bivalent preparations will help accelerate their decision to vaccinate against COVID-19. Conclusions: Bivalent vaccination is an important part of the fight against the ongoing COVID-19 pandemic. However, it is forecasted that its implementation will not contribute significantly to the increase in vaccination-related interest rate among those previously unvaccinated or only after the basic regimen. Therefore further observations in this direction are necessary.